Unveiling the epidemiology and community perspectives on bovine brucellosis in North Shewa, Central Highlands of Ethiopia - Aweke Engdawork; Abdela Bulbula; Awoke Melak; Haileleul Negussie (Scientific Reports)
Abstract Brucellosis is a bacterial disease of many domestic and wild animals with great economic and public health importance. Although it has a major constraint in dairy production, comprehensive information regarding the epidemiology of brucellosis in dairy herds is limited. Besides, evaluating the dairy farmers’ knowledge, attitude, and practice (KAP) regarding brucellosis is crucial for generating information that can enhance control programs and public health interventions. Thus, this study aims to investigate the seroepidemiology of brucellosis and evaluate the dairy farmers’ KAP in North Shewa, central highlands of Ethiopia. A total of 511 blood samples were randomly collected from 142 dairy herds. Rose Bengal plate test (RBPT) was used for primary screening, and a complement fixation test (CFT) was conducted on RBPT-positive samples. Retrospective information was collected to associate brucellosis with a history of reproductive disorders. A questionnaire survey assessed farmers’ knowledge, attitudes, and practices regarding zoonotic brucellosis. Multivariable Firth’s bias-reduced logistic regression model was used to identify factors associated with brucellosis seropositivity. The overall seroprevalence of brucellosis was 0.98% (95% CI: 0.41–2.34%) at the animal level and 3.52% (95%CI: 1.46–8.26%) at the herd level. Cows older than 6 years were four times more likely to be seropositive (OR = 3.82; 95% CI: 1.71–7.97; P = 0.004), while local breeds had a six-fold higher risk (OR = 6.2; 95% CI: 2.08–8.21; P = 0.016). Cattle with a history of abortion (OR = 22.35; 95% CI: 3.90-107.91; P = 0.002) and retained fetal membrane (OR = 18.74; 95% CI: 3.48–63.86; P = 0.020) showed significantly higher seroprevalence. A survey of 120 respondents found that 86% were unaware of zoonotic brucellosis, 74.63% assisted cows during the parturition without protective equipment, and 64% consumed raw meat. Only 9.17% disposed of fetal membranes and aborted fetuses properly. This study revealed evidence of brucellosis in 4% of dairy herds, poor understanding of the disease, various risky practices, and poor biosafety measures. Thus, educating dairy farmers and implementing strict farm biosecurity measures are essential steps to minimize the impacts of the disease on the growing dairy industry and public health.